Isolation and characterization of polyoma virus genomes with deletions between the origin of viral DNA replication and the site of initiation of translation in the early region. - Wells, R D (1979)
We introduced deletions in the early region of the polyoma virus genome near the HaeII restriction enzyme cleavage site, between the origin of viral DNA replication and the site of initiation of translation of the polyoma T antigens. We analyzed the DNA of the deletion mutants by restriction enzyme digestion. Four of the mutants had deletions beginning very close to the HaeII site and extending clockwise toward the site of initiation of translation. The deletions near the HaeII site varied in size from about 10 base pairs to about 55 base pairs. The mutants containing deletions near the HaeII site were capable of lytic growth in mouse 3T6 cells and were capable of transforming rat F2408 cells, as judged by focus formation.